Grundlegende Neuordnung' des EEG - aber wie? - Erik Gawel (Wirtschaftsdienst, 2013)
Die Sorge um erhöhte Strompreise, für die maßgeblich die EEG-Umlage verantwortlich sein soll, beherrscht zurzeit die öffentliche Diskussion zur Energiewende. Die Entwicklung der Umlage wurde zum Gradmesser der Kosten der Energieversorgung stilisiert, und der Ruf nach einer 'grundlegenden Neuordnung' des EEG zur Kostenbegrenzung immer vielstimmiger. Doch wie sollte eine solche Neuordnung aussehen und mit welchen Verbesserungen wäre überhaupt zu rechnen? – – The public debate on the German energy transition has recently been widely dominated by concerns about costs, particularly the role of the feed-in tariffs (FIT) of the German Renewable Energy Sources Act and its rising surcharge on electricity prices. The apportionment rate has been misleadingly taken as an indicator for societal transition costs. Hence, the calls for a fundamental reform of the German FIT scheme are growing louder, and manifold but competing concepts have been suggested so far. The paper deals with the question of how such a reform could look like and what might be really gained from developing the current FIT scheme.
Keywords: H23; Q42; Q48; 330; Förderung erneuerbarer Energien; Energiepreis; Deutschland